UTILIZACIÓN DE RESIDUOS AGROINDUSTRIALES PARA LA PRODUCCIÓN DE PROTEÍNA MICROBIANA - Acosta, Sonia Peñafiel; Zúñiga, Guido Brito; Shugulí, Gianela Muñoz; Peñafiel, Anabel Zabala; Moina, Ana Chafla (European Scientific Journal, ESJ, 2015)
The effect of including whey in a mix of maracuya peel and whole ripe banana was evaluated, including analysis of bromotalogical factors, pH, ammonia, short chain fatty acids, and count of yeast by fermentation in solid state every 12 hours. A randomized design in factorial arrangement was employed, with 3 repetitions. The results show that pH values increase independently at the beginning, however, during the fermentation time, the value differs between treatments. The contents of NH3 registered differences, obtaining a higher value in the treatment of 10% whey at 24 hours with the content of 24.72 meq/L, with respect of the lowest results with the control treatment. At 36 hours of fermentation time the values of NH3 reduced in all the treatments. The number of yeasts increased when they were treated with 5% and 10% of whey, with respect to the control in the treatment of 15%. A highly significant relationship exists between the production of short chain fatty acids and the fermentation time. The control treatment increased 0.083 mmol/100g per day, while the treatment of 10% whey experienced increases of 1.310 mmol/100g. The (MS) decreased at the same rate when the whey level increased, with respect to the first initial material. Upon increasing the fermentation time, the MS in the treatments increased, with respect to the control, which gives evidence of a greater increase in the treatment of 15% at 36 hours of fermentation time. The raw fiber decreased at growing levels of whey. The true protein increased at the rate that the whey level and the fermentation time increased in each treatment, being lowest in the control treatment.